Influence of Naproxen, Age and Body Mass Index on the Biological Composition of Leukocyte Rich Platelet-Rich Plasma: A Prospective, Therapeutic, Cohort Study. Issue 7 (30th July 2018) - Mannava, Sandeep; Whitney, Kaitlyn E.; King, Jillian; Kennedy, Mitchell; Klett, Katarina; Dornan, Grant; Chahla, Jorge; Evans, Thos A.; Huard, Johnny; LaPrade, Robert F.
Objectives: Platelet-rich plasma (PRP) is comprised of several biologically active factors that can stimulate musculoskeletal healing processes. Non-steroidal anti-inflammatory drugs (NSAIDs) are used to treat many musculoskeletal conditions and influence platelet function. The influence of NSAIDs on the biological composition of PRP is not well known. The purpose of this study was to quantify and compare growth factors and other chemokines and cytokines in leukocyte-rich PRP (LR-PRP) between baseline, following one-week of NSAID (Naproxen) use, and after a one-week washout period. We hypothesized that Naproxen would alter both the catabolic and anabolic factors in LR-PRP. Our secondary hypothesis was that discontinuing Naproxen use for one-week would be sufficient to return LR-PRP's molecular constituents back to baseline. Study Design: Non-randomized, prospective cohort study; Level of evidence: 2. Methods: Sixteen healthy volunteers (n=8 male and n=8 females) were enrolled in this IRB approved study. Peripheral blood was drawn at three-time points: baseline, one-week after Naproxen intake, and after a one-week washout period. Donors were instructed after the first blood-draw to ingest oral Naproxen tablets twice a day (440 mg bid) for one-week. Fifty-two anabolic and catabolic factors in LR-PRP were measured at all time points. Donor demographics were collected at the time of the initial blood-draw. To address the primary hypothesis of this study, Friedman's test was used to identify significant differences between the baseline, Naproxen and washout time points while accounting for the repeated measures design of this study. When Friedman's test was significant, pairwise comparisons were made using Holm's method to control the family-wise type 1 error rate. Results: Three anabolic growth factors, platelet derived growth factor-AA (PDGF-AA, Figure 1), platelet derived growth factor-AB (PDGF-AB, Figure 1), and transforming growth factor-β1 (TGF-β1), had a significant decline from baseline (p<0.05) after one-week of Naproxen use. There was a significant recovery (p<0.05) of PDGF-AA and PDGF-AB levels after the one-week washout of NSAIDs, with a return to baseline levels. TGF-β1 did not recover to baseline levels after a one-week washout period. Catabolic factors tumor necrosis factor-β (TNF-β) and interleukin-6 (IL-6) had a significant decline from baseline (p<0.05) after NSAID use for one-week and returned to levels similar to baseline (p<0.05) after a one-week washout period. Conclusion: Naproxen use diminished several biological factors in LR-PRP; however, a one-week washout period was sufficient for the recovery of PDGF-AA, PDGF-AB, TNF-β, and IL-6 to return to baseline levels. Our results suggest that patients undergoing PRP treatment should discontinue Naproxen, and other NSAID use, at least one-week prior to harvest and injection of PRP.